Determining the Effect of Immersion Duration in a Garlic Solution on the Freshness Level of Layang Fish (Decapterus macrosoma, Blecker) - Wenno, M. R.; Kaya, A. O. W.; Lewerissa, S.; Wattimena, M. L.; Sormin, R. B. D.; Nanlohy, E. E. E. M. (Research Advances in Environment, Geography and Earth Science Vol. 5, 2024)
The present study aimed to determine the effect of immersion duration in a garlic solution on the freshness level of layang fish. Fish degradation occurs mainly due to the activity of microorganisms. In addition, enzymatic and chemical reactions also cause fish quality degradation. Fish form part of a highly nutritional diet and provide a source of essential proteins. However, they can rapidly degrade, particularly when in a fresh state and not handled properly. Degradation can occur either biochemically or microbiologically. There are a number of techniques that can be used to preserve the quality of fresh fish, such as using natural preservatives like garlic. It has been demonstrated that the plant garlic prevents the growth of germs. Garlic tubers include antibacterial substances such ajoene and allicin (diallyl thiosulfinate). The Total Volatile Base Nitrogen (TVBN) values ranged from 25.33 mg%N to 78.66 mg%N, the bacterial TPC (Total Plate Count) was 7.5x101 to 1.6x105 CFU/g, and the pH 5.9 to 8.0. Visibility ranged from 4.64 to 8.33, odor 3.47 to 8.75, and texture 3.62 to 8.20. This study found that immersion treatment using garlic can maintain fish quality for eight hours, with a 20-minute immersion treatment obtaining optimal parameter values. Some natural ingredients including garlic solution can be used as preservatives to maintain the freshness of fish, these ingredients alone cannot preserve the freshness of fish for a long time, thus they need to be combined with cold temperatures. Ice and natural ingredients can synergize to maintain the freshness of fish for a longer period.